O EFEITO DA SINVASTATINA EM ALTERAÇÕES CARDIOVASCULARES E NA PERDA ÓSSEA INDUZIDA PELA PERIODONTITE - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
Periodontitis is a chronic inflammatory disease initiated and perpetuated by Gram-negative anaerobic bacteria that colonize the subgingival area. This disease is characterized by destruction of periodontal tissue insertion, bone resorption, leukocyte infiltration and formation of periodontal pockets. Studies show a significantly increased risk of cardiovascular disease, especially atherosclerosis and hypertension, among people with periodontitis. It is believed that systemic inflammation induced by periodontal disease and decreased nitric oxide bioavailability would cause endothelial dysfunction, which consequently leads to cardiovascular disease. Interestingly, studies show that statins that has been providing consistent and satisfactory results in reversal of endothelial dysfunction. Thus, the purpose of this study was to evaluate the effect of systemic administration of simvastatin on inflammatory parameters induced periodontitis and correlate their possible actions in the cardiovascular system and in alveolar bone loss. Wistar rats were subjected to induction of periodontitis by placement of ligatures or were subjected to false-surgery (the ligatures were immediately placed and removed). On day 8, the animals were randomized to treatment with simvastatin (10 mg/kg/day p.o.) or vehicle.During the experiment, on days 1, 7 and 14 the rats were prepared for analysis of systolic blood pressure and heart rate. And on day 14, the rats were prepared for analysis of cardiovascular parameters, lipid profile, systemic inflammatory markers and tissue injury. The maxilla and mandible were removed for analysis of bone loss. Our data show that animals with untreated periodontitis showed an endothelium-dependent vasodilator response (acetylcholine) reduced a characteristic of endothelial dysfunction in animals with periodontal disease. In contrast, we found an increased vasodilatory response in animals with periodontitis treated with simvastatin. The vascular changes induced by treatment with simvastatin were associated with a decrease in lipid profile, and lymphocytic inflammatory markers such as IL-6 and C-reactive protein, which are traditionally associated with cardiovascular risk. And interestingly, simvastatin decreased alveolar bone loss in animals with periodontitis. Our data show that simvastatin reduces alveolar bone loss, systemic inflammation and damage to the endothelium induced periodontitis. Thus, simvastatin can be considered a promising drug for the treatment of periodontal disease and prevention of cardiovascular complications.
Keywords: periodontite; inflamação sistêmica; disfunção endotelial; Sinvastatina; periodontitis, systemic inflammation; endothelial dysfunction; Simvastatin; CNPQ::CIENCIAS DA SAUDE::FARMACIA